2004
DOI: 10.1645/ge-287r
|View full text |Cite
|
Sign up to set email alerts
|

African Trypanosome Interactions With an in Vitro Model of the Human Blood–brain Barrier

Abstract: The neurological manifestations of sleeping sickness in man are attributed to the penetration of the blood-brain barrier (BBB) and invasion of the central nervous system by Trypanosoma brucei gambiense and Trypanosoma brucei rhodesiense. However, how African trypanosomes cross the BBB remains an unresolved issue. We have examined the traversal of African trypanosomes across the human BBB using an in vitro BBB model system constructed of human brain microvascular endothelial cells (BMECs) grown on Costar Transw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 51 publications
5
81
1
2
Order By: Relevance
“…A tenfold increase of the trypanosomal inoculum resulted in an increased transmigration of T. b. brucei and T. b. rhodesiense, but not of T. b. gambiense, indicating that a certain density of parasites has to be reached in order to achieve maximum transmigration rates. The invasion process occurs by opening of the tight junctions without the destruction or degradation of tight junction proteins, and trypanosomes transmigrate through the BBB paracellularly (Grab et al, 2004). Opening of the tight junctions has been proven by real-time TEER (transendothelial electrical resistance) measurements, which revealed a transient loss of barrier integrity during transmigration (Grab et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A tenfold increase of the trypanosomal inoculum resulted in an increased transmigration of T. b. brucei and T. b. rhodesiense, but not of T. b. gambiense, indicating that a certain density of parasites has to be reached in order to achieve maximum transmigration rates. The invasion process occurs by opening of the tight junctions without the destruction or degradation of tight junction proteins, and trypanosomes transmigrate through the BBB paracellularly (Grab et al, 2004). Opening of the tight junctions has been proven by real-time TEER (transendothelial electrical resistance) measurements, which revealed a transient loss of barrier integrity during transmigration (Grab et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For African trypanosomes paracellular transmigration of endothelia has been reported as well (Grab et al, 2004). To investigate whether paracellular transmigration of macrophages has synergistic effects on the transmigration of trypanosomes, as shown for lymphocytes in a rodent model (Masocha et al, 2004), the transmigration of J774 murine macrophages alone and together with T. b. brucei TC221 was examined.…”
Section: Trypanosomes Do Not Benefit From Macrophage Transmigrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The HBMEC monolayer cultured on Transwell insert has been broadly used as an in vitro BBB model (28,48,49). Based on the BBB model, we previously showed that A␤-induced CCR5 expression was related to T cells crossing the HBMEC monolayer (28).…”
Section: A␤-activated Signal Pathway From Rage To Egr-1 Is Required Fmentioning
confidence: 99%
“…38 Several studies have demonstrated that the use of subtherapeutic doses of diminazene aceturate may prolong survival of horses experimentally infected by T. brucei spp., but it is associated with subsequent invasion of the central nervous system by trypanosomes and production of necrotizing encephalitis. 14,18,19,26,28,34,39,44 Diminazene aceturate clears trypanosomes from tissues except in the central nervous system, 17 because the drug does not cross the blood-brain barrier (BBB). 19,31 Thus, trypanosomes in the central nervous system survive antitrypanosomal therapy, and with a change in their surface glycoproteins may lead to new parasitemias.…”
Section: Discussionmentioning
confidence: 99%